Analysis of Industry 4.0 Readiness among Regional Governments in Indonesia: The Worth of Digital Wisdom and Values in Public Services - Wawan Sobari; Ibnu Asqori Pohan; Nurizal Dwi Priandani (Puslatbang KDOD Lembaga Administrasi Negara, 2023)
This research aims to evaluate the readiness of regional governments to engage with the fourth Industrial Revolution (Industry 4.0), especially in e-service delivery. In the era of Industry 4.0, governments are increasingly considered public service centres that are evaluated for their ability to provide expanded services in the most efficient and individual ways. This research applied an eservice model survey by evaluating indicators of e-services about maturity values on a user-based website or mobile device applications. Assessments of e-service in three regional governments in Greater Malang reveal flaws in personnel readiness, user preparedness, flexibility in e-service procedures and requirements, integration among applications, lack of socialization, weak leader support and commitment, low budgets, and infrastructure constraints. Guided by these discoveries, unlike with theory, this study proclaims the importance of digital wisdom involving empathy, simplicity, compromise, creativity, and humility in public service. This study also formulates the digital values of political leadership transformation, public need-based digitalization, immediate resolution, changes in digital governance networks, digital wisdom, and interregional connectivity in public services. Finally, the study expands on the theory that governments can exceed preparedness by incorporating digital wisdom and values to drive public service.